Calculating the Temperature dependence Radiative recombination rate Coefficients for ions - A.Khalaf, Alaa (Al-Qadisiyah Journal of Pure Science, 2018)
Radiative recombination rate coefficients (RRC) are presented for several ions with open and closed shells, ( H I, He I, He II, N V, N VI, N VII) . The temperature of electron range 10-109 K is considered. The calculations have been performed in the framework of analytic fit parameters formula with no consideration of relativistic effects. Our results of RRC compared with the theoretical data available as a function of electron temperature, and the agreement was very good. Some data which had been depended showed a peak at high temperatures because of the influence of autoionizing resonance.